IMMUNOGLOBULIN SYNTHESIS AND SECRETION, III. INCORPORATION OF GLUCOSAMINE INTO IMMUNOGLOBULIN ON POLYRIBOSOMES - Sherr, Charles J. (1969)
Mouse myeloma cells were pulse-labeled in vitro with (3)H-D-glucosamine and (14)C-L-leucine. Analysis on sucrose gradients revealed incorporation of both isotopes into polyribosomes and release of most of such radioactivity after treatment of labeled cells in vitro with puromycin. A mixing experiment excluded the in vitro binding to unlabeled polyribosomes of (3)H-glucosamine in labeled post-ribosomal material. Polyribosomes labeled with (3)H-glucosamine were precipitated with antiserum specific for mouse immunoglobulin. By chromatography and gel filtration, the precipitable radioactivity was shown to be glucosamine covalently bound to heavy and light chains.